Effect of basal luteinizing hormone/follicle-stimulating hormone ratio on clinical outcome of In Vitro fertilization in patients with polycystic ovarian syndrome: a retrospective cohort study - Dan Shan; Junzhao Zhao; Xiaosheng Lu; Huina Zhang; Jieqiang Lu; Qi Shen (PeerJ)
Background The basal luteinizing hormone (LH) and the prior LH to follicle-stimulating hormone (FSH) ratio (LH/FSH) in polycystic ovarian syndrome (PCOS) are generally higher than those in non-PCOS patients and the general population. The potential negative effects of elevated LH on human reproductive function are highly controversial, as are the effects of down-regulation of LH on reproductive function. The purpose of this study was to evaluate the effect of the basal LH/FSH ratio on the live birth rate of PCOS patients undergoing in vitro fertilization (IVF) cycles. Methods A retrospective analysis was conducted on 698 patients with polycystic ovary syndrome undergoing IVF treatments with a mild stimulation protocol (n = 95) and a gonadotropin-releasing hormone (GnRH) agonist protocol (n = 603). The basal LH/FSH ratio of 2 was used as the cut-off value for further subgroup analysis. The demographic properties, controlled ovarian hyperstimulation (COH) processes, and clinical pregnancy outcomes were compared between groups under each ovulation stimulation protocol. Results The live birth rate for patients with a LH/FSH ratio ≥ 2 group (56.38%, n = 149) was not statistically different from that of the ones with a ratio < 2 (53.74%, n = 454) in the GnRH agonist protocol (P = 0.576). Correspondingly, the live birth rate for the LH/FSH ratio ≥ 2 group (43.48%, n = 23) also showed no statistical difference from the ratio < 2 group (48.61%, n = 72) in the mild stimulation protocol (P = 0.668). Additionally, LH/FSH ratios had no significant effect on the live birth rate after adjusting for confounders both in the GnRH agonist protocol (adjusted OR: 1.111; 95% CI [0.467–2.642], P = 0.812) and in the mild stimulation protocol (adjusted OR: 4.057; 95% CI [0.431–38.195], P = 0.221). Furthermore, there was no significant difference in the live birth rate between different ovulation stimulation protocols in PCOS patients with the LH/FSH ratio ≥ 2. Conclusions The live birth rate in IVF outcomes was not affected by an elevated basal LH/FSH ratio in patients with polycystic ovary syndrome. The choice of the GnRH agonist protocol or mild stimulation protocol for ovulation stimulation does not affect the final clinical outcomes either for PCOS patients with a basal LH/FSH ratio ≥ 2.